Correlation between self-efficacy and different strategies for coping with stressful situations in female handball players - Markovic, S.; Markovic, K.; Ristic, V.; Avramov, E. (XX Scientific Conference.FIS COMMUNICATIONS 2017" in physical education, sport and recreation (Nis, Serbia, october 19-21st, 2017), 2017)
Almost every competition, especially a championship or one of greater importance to an athlete, represents a "stressful situation", or more precisely an objective state that stimulates or causes stress. Numerous studies have shown that self-efficacy, as one of socio-psychological factors, affects the way of overcoming stressful situations in sports. The aim of this research is to determine the correlation of self-efficacy with different strategies for dealing with stressful situations in female handball players who, during the testing period, competed at the highest level of national handball competition of the Republic of Serbia. There were 15 participants in this study. Variables in the research: Strategies for overcoming stressful situations and Self-efficacy. Tests were conducted to determine the significance of correlation between strategies of overcoming stress and self-efficacy. The obtained data analyzed using the program for statistical data processing IBM SPSS Statistics 19.